Studi Fenomenologi Pengalaman Hidup Pasien Ca Mamae Dalam Menjalani Kemoterapi - Amelia, Sherly; Dewi, Ratna; Manelsa, Feby Tri (Universitas Fort De Kock Bukittinggi, 2020)
In breast cancer Chemotherapy is given at an advanced stage and has spread (Aziz, 2001). chemotherapy can cause very bad physical conditions that can cause physiological and psychological effects. Physiological effects that can occur are fatigue, lethargy, hair loss, intestinal disorders and oral cavity. Dr. Achmad Mochtar Bukittinggi Hospital with breast cancer sufferers has increased in the last two years This study aims to explore the life experiences of breast cancer patients in undergoing chemotherapy at RSUD Dr. Achmad Mochtar Bukittinggi.This type of qualitative research with a phenomenological approach was carried out in January 2020. The sampling technique was purposive sampling with a participant of 4 people and the technique of data collection was through in-depth interviews.Based on the results of research on the phenomenological study of the experience of patients ca mamae in undergoing chemotherapy produced themes: 1) Physical, pscyhological responses experienced in undergoing chemotherapy, 2) Striving for healing and recovery, 3) Physical discomfort as an impact of participants in undergoing chemotherapy,This study concludes that good participant knowledge about breast cancer along with the signs and symptoms felt by the participants, so that participants immediately take treatment. Hopefully the results of this study can be a reference for future researchers Keywords: life experience, breast cancer, chemotherapy, patients